Pengaruh Metode Outdoor Learning Terhadap Minat Belajar Siswa dalam Mata Pelajaran IPA Sekolah Dasar - Nurhafizah; Mustika, Dea (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The influence of the Outdoor Learning method on students' interest in learning science subjects in grade III of SD 023 Pandau Jaya. The formulation of the problem in this study